2011
DOI: 10.1242/jeb.058438
|View full text |Cite
|
Sign up to set email alerts
|

Symmorphosis and the insect respiratory system: allometric variation

Abstract: SUMMARYTaylor and Weibel's theory of symmorphosis predicts that structures of the respiratory system are matched to maximum functional requirements with minimal excess capacity. We tested this hypothesis in the respiratory system of the migratory locust . Therefore, the principles of symmorphosis are upheld at each step of the oxygen cascade in the respiratory system of the migratory locust. Supplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 70 publications
(91 reference statements)
2
36
2
Order By: Relevance
“…Maximum oxygen uptake by flight muscle during tethered flight is 967±76molh -1 g -1 (body mass specific, ±95% confidence interval CI), whereas the hopping muscles consume a maximum of 158±8molh -1 g -1 during jumping. The 6.1-fold difference in aerobic capacity between the two muscles is matched by a 6.4-fold difference in tracheole lumen volume, which is 3.5ϫ10 g Insect respiratory symmorphosis An allometric assessment of the migratory locust Locusta migratoria respiratory system has shown that throughout ontogeny the hopping muscles' aerobic capacity scales in proportion with the total volume, surface area and anatomical diffusing capacity of the tracheoles, and the total volume and inner membrane surface area of the mitochondria (Snelling et al, 2011b). The study therefore provides strong evidence that the insect respiratory system conforms to the economic design principles of symmorphosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Maximum oxygen uptake by flight muscle during tethered flight is 967±76molh -1 g -1 (body mass specific, ±95% confidence interval CI), whereas the hopping muscles consume a maximum of 158±8molh -1 g -1 during jumping. The 6.1-fold difference in aerobic capacity between the two muscles is matched by a 6.4-fold difference in tracheole lumen volume, which is 3.5ϫ10 g Insect respiratory symmorphosis An allometric assessment of the migratory locust Locusta migratoria respiratory system has shown that throughout ontogeny the hopping muscles' aerobic capacity scales in proportion with the total volume, surface area and anatomical diffusing capacity of the tracheoles, and the total volume and inner membrane surface area of the mitochondria (Snelling et al, 2011b). The study therefore provides strong evidence that the insect respiratory system conforms to the economic design principles of symmorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…The fixation and embedding process was performed over 5 consecutive days as detailed in an earlier study (Snelling et al, 2011b), and was identical for flight and hopping muscle. Briefly, immediately following dissection, the tissue pieces were immersed into a chemical fixative solution of 2.5% glutaraldehyde and 2% formaldehyde in 0.2moll -1 phosphate buffer with pH7.4.…”
Section: Fixation and Embeddingmentioning
confidence: 99%
See 3 more Smart Citations